Estudo paramétrico sobre o dimensionamento de cortinas autoportantes utilizando métodos de equilíbrio limite - Castorina Fernanda da Silva Vieira (2002)
The paper presents a parametric study on the design of flexible cantilever retaining walls using classical limit equilibrium methods, namely the UK method and USA method. The conventional approaches of introducing safety in the calculations are referred to as well as the Cases B+C approach established in Eurocode 7. The results of the design, in particular the wall embedded height and the maximum bending moment, provided by the distinct approaches are presented for a large range of shearing resistance parameters, two conditions of the soil-to-wall interface and distinct positions of the water table. The reduction of safety due to an overexcavation equal to 10% of the excavation depth is evaluated.